1999
DOI: 10.1128/mcb.19.6.4047
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Characteristics of Calpain 3 Isoforms Generated through Tissue-Specific Transcriptional and Posttranscriptional Events

Abstract: Calpain 3 is a nonlysosomal cysteine protease whose biological functions remain unknown. We previously demonstrated that this protease is altered in limb girdle muscular dystrophy type 2A patients. Preliminary observations suggested that its gene is subjected to alternative splicing. In this paper, we characterize transcriptional and posttranscriptional events leading to alterations involving the NS, IS1, and IS2 regions and/or the calcium binding domains of the mouse calpain 3 gene (capn3). These events can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
105
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 40 publications
3
105
1
Order By: Relevance
“…The ex 6Ϫ Tg showed no activity above non-Tg control muscle, even though expression levels of this transgene were approximately 60-fold higher than endogenous C3. Because it has been demonstrated in vitro that ex 6Ϫ constructs retain some proteolytic activity, it cannot be concluded that all C3 activity is abolished when this transgene is overexpressed (5). However, these data suggest that extracts from ex 6Ϫ Tg may have reduced C3 proteolytic activity compared with non-Tg and show that extracts from mice ex- pressing full-length C3 and ex 15Ϫ Tg produce higher C3 activity than extracts from non-Tg mice.…”
Section: Activity Of C3 Transgenes In Zymogramscontrasting
confidence: 40%
See 2 more Smart Citations
“…The ex 6Ϫ Tg showed no activity above non-Tg control muscle, even though expression levels of this transgene were approximately 60-fold higher than endogenous C3. Because it has been demonstrated in vitro that ex 6Ϫ constructs retain some proteolytic activity, it cannot be concluded that all C3 activity is abolished when this transgene is overexpressed (5). However, these data suggest that extracts from ex 6Ϫ Tg may have reduced C3 proteolytic activity compared with non-Tg and show that extracts from mice ex- pressing full-length C3 and ex 15Ϫ Tg produce higher C3 activity than extracts from non-Tg mice.…”
Section: Activity Of C3 Transgenes In Zymogramscontrasting
confidence: 40%
“…In addition, overexpression of calpastatin, the calpainspecific inhibitor (9,10), also blocks muscle cell differentiation in vitro. Furthermore, alternatively spliced C3 isoforms lacking portions of either IS1and͞or IS2 have been observed in developing human and mouse skeletal muscle by using reverse transcription-PCR (5). After birth, expression levels of the deletion isoforms decline and the full-length, mature isoform predominates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In transgenic mice overexpression of p94⌬ex6 or p94⌬ex15, but not full-length p94WT, blocked/delayed maturation of myofibers (34). These variants, which were shown to be less active than p94 especially with regard to autolytic activity (29), could act detrimentally at various developmental stages. Thus, these previous data and our data are in support that both the transient expression and the disappearance of p94 isoforms at the early stages of myogenesis are important for myotube maturation, probably because these isoforms respond differently to the cellular mechanisms regulating p94.…”
Section: Regulated Expression Of P94⌬ex During Muscle Development Andmentioning
confidence: 99%
“…Because previous studies have revealed that mouse embryonic muscles express p94 variants without exons 6, 15, and/or 16 (29), the relative abundance of transcripts resulting from those exon-skipping events was examined (Fig. 1A).…”
Section: Transcription Of the P94 Gene During Myofibrillogenesis-ex-mentioning
confidence: 99%